Penerapan Ice Breaking sebagai Strategi untuk Meningkatkan Motivasi Belajar Siswa - Lisnawati Lisnawati; Muhammad Munir; Andri Afriani (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2025)
This study aims to determine the effect of the application of Ice Breaking in increasing student learning motivation. The method used is quantitative with a pre-experimental one-group pretest-posttest design. Data were collected through questionnaires, observations, and documentation, then analyzed using simple linear regression and product moment correlation tests. The results showed that there was an increase in learning motivation after the implementation of ice breaking. The average pretest score of 40.23 increased to 40.35 in the posttest. The correlation test showed a value of r = 0.7 > r table 0.388, which means there is a significant relationship between ice breaking and learning motivation. The regression equation obtained is Y = 17 + 0.65X with a coefficient of determination of 49%, meaning that Ice Breaking contributed 49% to increasing learning motivation. These findings indicate that the use of Ice Breaking is an effective strategy in supporting active and enjoyable learning in elementary classes, especially in science learning.